Characterisation of the Oscillatory Flow Reactor for the Fermentation of Escherichia coli - Norfaezahtul, Nor Azaini; N., Masngut (Malaysian Society of Applied Biology, 2018)
Oscillatory Flow Reactor (OFR) is a novel type of tubular reactor consists of an equally spaced orifice baffles fitted inside the column of the reactor. The mixing in the OFR can be controlled by a combination of geometrical (i.e. baffles and orifice diameter) and operational parameters (i.e. oscillation frequency). The aim of this work was to develop and characterizes the novel OFR as a bioreactor. Upon completion of the OFR development, the reactor was subjected to a certain experiment for bioreactor characterization. The parameters studied were temperature profile, volumetric mass transfer coefficient (kLa), water loss due to evaporation and sterilization hold. The results showed the OFR was able to maintain the set temperature and its sterility throughout the experiment duration of 24 hours. The water loss due to evaporation inside the OFR was negligible as it was less than 4%. The highest kLa obtained was 33.6 h-1 at an oscillation frequency of 5 Hz. The OFR has shown its suitability as a bioreactor through various experiments conducted and will be tested for the fermentation of E. coli in the future.